Pengaruh Celebrity Endorser, Citra Merek, dan Kualitas Produk Terhadap Keputusan Pembelian Air Minum Dalam Kemasan Le Minerale di Kota Depok - Maulana Rizki Saputra; Irwandu Dananjaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Increasingly advanced technology and changing lifestyles in modern society have influenced consumption patterns for basic necessities, including drinking water. High mobility, busy work schedules, and the need to save time encourage people to choose products that are practical, efficient, and easily accessible. In this context, bottled drinking water (AMDK) is a primary solution, not only because it is practical but also because it meets the quality and safety standards consumers expect. This study examines how Depok City consumers' decisions to purchase Le Minerale bottled drinking water are influenced by brand image, product quality, and celebrity endorsers. For this quantitative study, primary data was gathered via a questionnaire. 180 respondents were then sampled after 30 respondents took part in instrument testing to evaluate validity and reliability. Purposive sampling and non-probability sampling were combined in the sample strategy. Multiple linear regression, the coefficient of determination (R2), normality, heteroscedasticity, multicollinearity, validity, reliability, and hypothesis testing were all included in the SPSS analysis of the data.The study's findings demonstrate that Le Minerale buying decisions are significantly influenced by brand image, product quality, and celebrity endorsers. However, brand image elements only slightly influence Le Minerale buying decisions when compared to other aspects like product quality and celebrity endorsements.